2022
DOI: 10.1021/acs.energyfuels.1c03364
|View full text |Cite
|
Sign up to set email alerts
|

Development of Artificial Neural Network Models for the Simulation of a CaCO3 Scale Formation Process in the Presence of Monoethylene Glycol (MEG) in Dynamic Tube Blocking Test Equipment

Abstract: The precipitation of gas hydrate and inorganic salts (scale) during oil and gas production represents a significant flow assurance hindrance for the industry. Chemical inhibitors can prevent the fouling process, but specific inhibitors to address a problem could result in synergistic or adverse effects. Simulations in tubes and pipelines are necessary to understand these behaviors by assessing the scaling tendency of the water. The primary objective of this study was to create models using an artificial neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…15 Ferreira and Santos developed artificial neural network models to simulate the calcium carbonate scaling formation process in the presence of gas hydrate inhibitor monoethylene glycol. 16 Arenas-Blanco and Meji ́a-Ospino evaluated a sulfonated graphene oxide (SGO) nanofluid on the interfacial properties of light and medium crude oil−water systems. They showed that the sulfonation process can improve the thermal stability and formation of stable emulsions.…”
Section: ■ Asphaltene Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…15 Ferreira and Santos developed artificial neural network models to simulate the calcium carbonate scaling formation process in the presence of gas hydrate inhibitor monoethylene glycol. 16 Arenas-Blanco and Meji ́a-Ospino evaluated a sulfonated graphene oxide (SGO) nanofluid on the interfacial properties of light and medium crude oil−water systems. They showed that the sulfonation process can improve the thermal stability and formation of stable emulsions.…”
Section: ■ Asphaltene Sciencementioning
confidence: 99%
“…Savulescu and co-workers used a low-field nuclear magnetic resonance (NMR) technique to characterize the evolution of wax mobility during wax crystallization by measuring the relaxation time . Ferreira and Santos developed artificial neural network models to simulate the calcium carbonate scaling formation process in the presence of gas hydrate inhibitor monoethylene glycol . Arenas-Blanco and Mejía-Ospino evaluated a sulfonated graphene oxide (SGO) nanofluid on the interfacial properties of light and medium crude oil–water systems.…”
Section: Flow Assurance Enhanced Oil Recovery (Eor) and Carbon Captur...mentioning
confidence: 99%
“…Therefore, an increasing number of scholars are exploring how to leverage machine learning to fully utilize the massive amount of data from oil fields to address the increasingly complex on-site production conditions. Researchers such as Zhao [23], Gabetta, G. [24], Paulo A. Paz [25], Wang [26], and Bruno X. Ferreira [27] have integrated machine learning into scaling considerations and achieved significant results.…”
Section: Introductionmentioning
confidence: 99%